Knowledge, attitudes and practices on postoperative pain management among registered nurses in a private hospital in Selangor-Malaysia - Norini binti Samad; Aini Ahmad; Puziah Yusof; Annamma Kunjukunju (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Postoperative pain is an important aspect of patient care. It occurs when there is tissue injury and muscle spasms following surgery. The goal of postoperative pain management is to minimize discomfort and side effects. Poor pain management can result in patient discomfort, complications, slow recovery, and longer hospitalization. Therefore, it is crucial for registered nurses to have a good understanding of postoperative pain assessment tools in order to provide the best pain management for their patients.Purpose: To assess knowledge and attitude related to pain management practices among registered nurses (rn) in postoperative patients. Method: In this study, a descriptive quantitative cross-sectional survey design was used. A questionnaire was administered, consisting of four parts. The first part collected socio-demographic data from Registered Nurses. The second part contained 13 true and false questions to evaluate their knowledge level. The third part consisted of 14 questions to assess the attitudes of Registered Nurses, and the fourth part consisted of 18 questions using a Likert scale to evaluate their practices. The total number of respondents was 108 Registered Nurses. The data obtained were analyzed using IBM Social Packages for the Social Sciences (SPSS) software version 26.Results: The study finding shows that  58.2% of Registered Nurses possess adequate knowledge regarding postoperative pain management, while 41.8% lack sufficient knowledge. These nurses agree that effective analgesia is crucial in postoperative care, with 90.8% recognizing the importance of pain measurement instruments. Providing a clean and comfortable ward with a neatly made bed is the most commonly practiced intervention for pain relief among Registered Nurses. Additionally, the study found a positive correlation between age, years of clinical experience, and pain management practices.Conclusion: According to the findings, there is significant variation in the knowledge, attitude, and practices of registered nurses when it comes to managing postoperative pain. To ensure that patients receive helpful and effective pain management after surgery, it is important for nurses to participate in ongoing professional development activities.